2023
DOI: 10.3390/ani13061118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Improved Microclimate Conditions on Growth and Physiological Performance of Two Japanese Quail Lines

Abstract: Microclimate parameters (ammonia, ambient temperature, heat index, and relative humidity) surrounding birds affect the production and health status of poultry. Therefore, this study aimed to evaluate the impact of adding natural zeolite to the litter of Japanese quail on improving microclimate parameters and its reflection in growth performance, blood gases, and blood biochemical parameters. A total of 1152 chicks were obtained from the same hatch at the 20th selection generation. Chicks were allocated into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The alteration of physiological indices can affect characteristics related to the health of birds ( Emam et al, 2023 ). As reported in Table 6 , dietary supplementation of AM significantly (linear and quadratic) influenced hepatic and renal functions (total protein, albumin, and albumin/globulin ratio, ALT, AST, creatinine, and urea, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The alteration of physiological indices can affect characteristics related to the health of birds ( Emam et al, 2023 ). As reported in Table 6 , dietary supplementation of AM significantly (linear and quadratic) influenced hepatic and renal functions (total protein, albumin, and albumin/globulin ratio, ALT, AST, creatinine, and urea, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in metabolic and physiological processes may have an impact on aspects of avian health ( Emam et al, 2023 ). Dietary (D + S) supplementation increased the serum biochemical indices of broiler chicks.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, D + S can be used as a prebiotic to improve the health of birds because of its affirmative influence on biochemical parameters such as the antioxidative components. Emam et al (2023) showed that physiological changes and metabolic processes can impact characteristics concerning the health of chicks. AL Suwaiegh (2023) reported that using green microalgae in feeding leads to enhanced hepatic function activity, resulting in higher albumin levels, as shown in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, variations in metabolic and physiological processes tend to affect relevant aspects of animal health ( 30 ). When liver cells are damaged by inflammation, toxicity, necrosis, etc., transaminases are released into the bloodstream and serum transaminases are elevated ( 31 ).…”
Section: Discussionmentioning
confidence: 99%